Network Pharmacology Combined With Metabolomics Reveals the Mechanism of Yangxuerongjin Pill Against Type 2 Diabetic Peripheral Neuropathy in Rats - Jin R; Pei H; Yue F; Zhang X; Zhang Z; Xu Y; Li J (Drug Design, Development and Therapy)
Ran Jin,* Hailuan Pei,* Feng Yue, Xiaodi Zhang, Zhicong Zhang, Yi Xu, Jinsheng Li Beijing Tongrentang Technology Development Co., Ltd. Pharmaceutical Factory, Beijing, 100079, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yi Xu; Jinsheng Li, Beijing Tongrentang Technology Development Co., Ltd. Pharmaceutical factory, Beijing, 100079, People’s Republic of China, Tel +86-10-87632655, Email xy706@sina.com; yarily@126.comPurpose: This study aims to explore the mechanism of Yangxuerongjin pill (YXRJP) in the treatment of diabetic peripheral neuropathy (DPN) by network pharmacology and metabolomics technology combined with animal experiments, and to provide scientific basis for the treatment of DPN.Methods: In this study, network pharmacology analysis was applied to identify the active compounds, core targets and signal pathways, which might be responsible for the effect of DPN. The DPN model was established by high-fat diet combined with streptozotocin (STZ) injection, and the rats were given administration for 12 weeks. The body weight, thermal withdrawal latency (TWL), sciatic motor nerve conduction velocity (MNCV), biochemical indexes, pathological sections of sciatic nerve, oxidative stress factors and the expression levels of neuroprotection-related proteins were detected. Metabolomics technology was used to analyze the potential biomarkers and potential metabolic pathways in DPN treated with YXRJP.Results: The results of network pharmacology showed that YXRJP could treat DPN through baicalin, β-sitosterol, 7-methoxy-2-methylisoflavone, aloe-emodin and luteolin on insulin resistance, Toll-like receptor (TLR), tumor necrosis factor (TNF) and other signaling pathways. YXRJP can prolong the TWL, increase the MNCV of the sciatic nerve, alleviate the injury of the sciatic nerve, reduce the levels of triglyceride (TG), improve the expression of Insulin-like growth factor 1 (IGF-1) protein in the sciatic nerve, and reduce the expression of protein kinase B (AKT) protein. Metabolomics results showed that the potential metabolic pathways of YXRJP in the treatment of DPN mainly involved amino acid metabolism such as arginine, alanine, aspartic acid, lipid metabolism and nucleotide metabolism.Conclusion: YXRJP can effectively improve the symptoms of DPN rats and reduce nerve damage. The effects are mainly related to reducing oxidative stress injury, promoting the expression of neuroprotection-related proteins, reducing the expression of inflammation-related proteins, and affecting amino acid metabolism, lipid metabolism, and nucleotide metabolism pathways. Our findings revealed that YXRJP has a good therapeutic potential for DPN, which provides a reference for further studies on YXRJP. Keywords: Yangxuerongjin pill, Type 2 Diabetes, Rat, peripheral neuropathy, network pharmacology, metabolomics